Correlated Equilibrium in Stochastic Games - Eilon Solan; Nicolas Vieille (Northwestern University, Kellogg School of Management, Center for Mathematical Studies in Economics and Management Science, 1998)
We study the existence of correlated equilibrium payoff in stochastic games. The correlation devices that we use are either autonomous (they base their choice of signal on previous signals, but not on previous states or actions) or stationary (their choice is independent of any data, and is drawn according to the same probability distribution at every stage). We prove that any n-player stochastic game admits an autonomous correlated equilibrium payoff, and obtain a stronger result for recursive games. When the game is positive and recursive, a stationary correlated equilibrium payoff exists.
Keywords: 330